Adaptation of Red Sea Phytoplankton to Experimental Warming Increases Their Tolerance to Toxic Metal Exposure - Kottuparambil, Sreejith; Jin, Peng; Agusti, Susana (Frontiers in Environmental Science, 2019)
Our recent study has demonstrated the rapid adaptation of the Red Sea phytoplankton to ocean warming, with associated constraints of physiological performance. However, the possible tradeoff between thermal adaptation and the organism’s tolerance to other environmental drivers in a warmer future scenario remains understudied. Here, we designed an evolutionary selection environment where the Red Sea diatom Chaetoceros tenuissimus was adapted to ambient (26 oC) and warming (30 oC) temperature scenarios for over 2000 generations. These strains were subsequently exposed to a range of copper (Cu) dose over three assay temperatures (26 oC, 30 oC, and 35 oC), to assess whether the adaptation to experimental warming is accompanied by a reformed tolerance to toxic pollutants. Most previous studies on Cu toxicity in marine phytoplankton were conducted within a small range of temperature (20−25 oC), indicating the need for further assessments to reveal the potential complex interactive effects between pollutants and more significant warming in the future. The acute Cu toxicity was estimated in terms of reduction in cell abundance (cells mL−1), growth rate (μ) and PSII photosynthetic efficiency (Fv/Fm), with 48 h median effective concentration values (EC50) varying from 2.22−20.19 μg L−1. We found a statistically significant interaction between assay temperature, selection temperature, and Cu doses in all the criteria tested. However, under extreme warming scenario (35 oC), the Cu sensitivity was significantly reduced, indicating cumulative antagonistic effects between these factors. Adaptation of phytoplankton to higher temperatures may help maintain their heavy metal tolerance, although a shift in temperature during the tests clearly altered their sensitivities. We conclude that selection for warming having made cells more resistant to Cu at the selection temperature in comparison to ambient-adapted population tested at 26 ºC. However, in warming-adapted cells, this was traded off against cupper resistance at 26 ºC.